Development of a Simple and Powerful Analytical Method for Formaldehyde Detection and Quantitation in Blood Samples - Yong-Hyun Kim; Jeongsik Park (Journal of Analytical Methods in Chemistry)
Human beings are easily exposed to formaldehyde (FA) in a living environment. Entry of FA into the human body can have adverse effects on human health, depending on the FA concentration. Thus, a quantitative analysis of FA in blood is necessary in order to estimate its effect on the human body. In this study, a simple and rapid analytical method for the quantitation of FA in blood was developed. The total analysis time, including the pretreatment procedure, was less than 20 min. To ensure a stable analysis, blood samples were stabilized using tripotassium ethylenediaminetetraacetic acid solution, and FA was selectively derivatized using 2,4-dinitrophenylhydrazine as pretreatment procedures. The pretreated samples were analyzed using a high-performance liquid chromatography-UV system, which is the most common choice for analyzing small-molecule aldehydes like formaldehyde. Verification of the pretreatment methods (stabilization and derivatization) using FA standards confirmed that the pretreatment methods are highly reliable in the calibration range 0.012–5.761 ng μL–1 (slope = 684,898, R2 = 0.9998, and limit of detection = 0.251 pg·μL–1). Analysis of FA in the blood samples of a Yucatan minipig using the new method revealed an average FA concentration of 1.98 ± 0.34 ng μL–1 (n = 3). Blood samples spiked with FA standards were analyzed, and the FA concentrations were found to be similar to the theoretical concentrations (2.16 ± 0.81% difference). The method reported herein can quantitatively analyze FA in blood at a sub-nanogram level within a short period of time and is validated for application in blood analysis.